[P01] Eligibility of COmmoN FEmoral Artery AtheroSclerotic DiSease for Endovascular Treatment: The CONFESS Study. (November 2022) - Kaneta, Gabriela; Husain, Shehzeen; Musto, Liam; Hamakarim, Tatiana; Elsharkawi, Ahmed; Littlejohn, Sofia; Helm, Jessica; Saratzis, Athanasios; Zayed, Hany
Abstract : Objective: Despite advances in endovascular technologies, the proportion of common femoral artery (CFA) lesions treated with endarterectomy (CFAE) which would be amenable to endovascular treatment with modern technologies is unknown. This study aimed to describe the morphology and composition of CFA lesions treated with surgical reconstruction in two high volume centres and report the proportion that would be amenable to endovascular treatment. Methods: All consecutive patients presenting with symptomatic peripheral arterial disease from January 2014 to December 2018 who underwent CFAE were included. Extensive data relating to the anatomy and morphology of the CFA atherosclerotic lesions were collected, including in depth analysis of the composition of the CFA plaque using three dimensional reconstruction based on computed tomography angiography. Results: A total of 829 CFAs in 737 patients were included (mean age 71 ± 10 years; 526 males, 71%); 451 (62%) presented with critical limb threatening ischaemia. Overall, 271 CFAs (33%) had a severe calcium load (> 1.1 cm³) that would have required stenting; 376 (45%) target vessels had a calcium load < 1.1 cm ³ with a patent CFA, profunda femoral artery (PFA), and proximal superficial femoral artery (SFA) and therefore would have been amenable to less complex endovascular treatment. Four (0.5%) target vessels were characterised by an occlusion of the CFA, external iliac artery (EIA), SFA), and PFA, and 642 (77%) by a patent CFA, PFA, and EIA. Conclusion: A significant proportion of patients with atherosclerotic CFA lesions who undergo surgery could potentially be candidates for endovascular treatment. A randomised trial comparing CFAE and new endovascular techniques in this clinical context is urgently required.